2003
DOI: 10.1037/0022-3514.84.6.1172
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment, the transition to parenthood, and depressive symptoms.

Abstract: Testing a model suggested by J. Bowlby (1988), this study investigated how a personal vulnerability (attachment ambivalence) interacts with perceptions of deficient spousal support before and during a major life stressor (the transition to parenthood) to predict pre-to-postnatal increases in depressive symptoms. Highly ambivalent women who entered parenthood perceiving either less support or greater anger from their husbands experienced pre-to-postnatal increases in depressive symptoms at 6 months postpartum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
189
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(215 citation statements)
references
References 88 publications
19
189
1
6
Order By: Relevance
“…Furthermore, theoretically important effects of attachment anxiety are obtained even when measures of neuroticism are statistically controlled (e.g. Mikulincer et al, 2002;Simpson, Rholes, Campbell, Tran, & Wilson, 2003).…”
Section: Insecure Attachment and Personality Pathologymentioning
confidence: 99%
“…Furthermore, theoretically important effects of attachment anxiety are obtained even when measures of neuroticism are statistically controlled (e.g. Mikulincer et al, 2002;Simpson, Rholes, Campbell, Tran, & Wilson, 2003).…”
Section: Insecure Attachment and Personality Pathologymentioning
confidence: 99%
“…Perhaps this occurs because these mothers lack the motivation, social skills, or supportive social networks necessary for seeking assistance. Simpson, Rholes, Campbell, Tran, and Wilson (2003) reported that the period immediately after delivery could be managed using the typical withdrawn style. However, withdrawn mothers soon realize that they need a tremendous amount of help and lose control over their daily activities as a result of childcare, which could lead to depression.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance refers to the degree to which individuals maintain psychological and emotional independence from significant others and desire to limit intimacy, characteristics associated with representations of others. While individuals who score low in both dimensions have secure working models (i.e., they consider themselves to be worthy of support and love and believe others to be trustworthy and supportive), individuals who score high in one or both of these dimensions present insecure working 7 | Journal of Clinical Psychology in Medical Settings models of the self (i.e., they believe they are unworthy of support) and/or of others (i.e., they believe other people are unsupportive of them; Griffin & Bartholomew, 1994;Simpson, Rholes, Campbell, Tran, & Wilson, 2003).…”
Section: Attachment Representations and Stress-inducing Conditionsmentioning
confidence: 99%